2003
DOI: 10.1111/j.1365-2621.2003.tb09614.x
|View full text |Cite
|
Sign up to set email alerts
|

Caliciviruses: A Major Cause of Foodborne Illness

Abstract: The public health impact of infections by human caliciviruses (HuCVs) is increasingly being recognized. The Norwalk-like viruses (NLV) are the most common cause of outbreaks of nonbacterial gastroenteritis and the most recognized foodborne viral etiologic agents. Factors that contribute to their high burden of infection are low infectious dose, stability in the environment, the diversity of strains, and the lack of long-term immunity to infection or illness. The recent development of sensitive molecular techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 106 publications
0
9
0
Order By: Relevance
“…Food is a frequent vehicle for human NoV transmission due to contamination with human fecal material (Gerba and Kayed 2003;Atmar 2010), poor personal hygiene of food workers and virus survival on/in the food and environment (Rzezutka and Cook 2004). The foodborne viruses in Europe network (FBVE) reported that between 2001 and 2007 data from over 10,000 outbreaks were analyzed, which showed that the proportion of foodborne outbreaks varied greatly between countries, but using predictive models, foodborne outbreaks were estimated to be around 50% (Verhoef et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Food is a frequent vehicle for human NoV transmission due to contamination with human fecal material (Gerba and Kayed 2003;Atmar 2010), poor personal hygiene of food workers and virus survival on/in the food and environment (Rzezutka and Cook 2004). The foodborne viruses in Europe network (FBVE) reported that between 2001 and 2007 data from over 10,000 outbreaks were analyzed, which showed that the proportion of foodborne outbreaks varied greatly between countries, but using predictive models, foodborne outbreaks were estimated to be around 50% (Verhoef et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that noroviruses cause more than 67% of all foodborne infections, but this is likely understated because of lacks of reporting, culturing, and detection methods (18,19,22). Noroviruses are highly infectious, easily transmissible, resistant to environmental stress, and ubiquitous; thus, contamination can occur anywhere in the food chain, from preharvest to point of service (10,13,28,37). Fresh produce becomes a significant vehicle in transmission of noroviruses because it undergoes minimal processing before consumption.…”
mentioning
confidence: 99%
“…Norovirus is believed to be the most common cause of foodborne illness in the United States and has caused numerous outbreaks on cruise ships, in hospitals, and in educational institutions (7,8). Environmental transmission via contaminated hands and fomites is believed to be a major route of transmission (9).…”
mentioning
confidence: 99%